Pengetahuan, Sikap, dan Perilaku Remaja dalam Mencegah Penyakit Menular Seksual: Sebuah Penelitian Korelasi - Dewanti, Nisa; Budiarti, Tamara Nur; Diana, Meli; Riesmiyatingdyah (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Background: The increasing number of sexually transmitted diseases (STDs) among young adults aged between 15 and 24 years remains a major problem of concern worldwide. Adolescents' poor knowledge regarding sexual and reproductive health, as well as the many misunderstandings regarding sexual issues, can cause adolescents to commit acts that risk increasing the incidence of sexually transmitted diseases. Objectives: This study aims to analyzed the correlation between knowledge, attitudes, and behaviors of adolescents in preventing sexually transmitted diseases. Methods: The study used cross sectional designed. This study was conducted at a vocational school in Sidoarjo, East Java, in December 2023. Sample in this study were vocational school’s students who were members of health extracurriculars. The sample size in this study was 50 respondents. This study used random sampling technique. This study used questionnaire as the instrument. Data analyzed used Kendall Tau b correlation method. Results: Most of the respondent were female (72%) and aged of sixteen (60%). The respondent’s knowledge about STDs was correlated with behavior to prevent STDs (p-value <0,01). The respondent knowledge about STDs was correlated with attitudes towards preventing STDs (p-value <0,01). The respondent attitudes towards preventing STDs was correlated with behavior to prevent STDs (p-value <0,01). Conclusion: There was a significant correlation between knowledge about STDs and attitudes towards preventing STDs, a significant correlation between knowledge about STDs and behavior to prevent STDs, and a significant correlation between attitudes and behaviors to prevent STDs